Bonding of wood with the adhesive from waste polystyrene - ŠERNEK, MILAN; KORDIŠ, ALJAŽ (Anali PAZU, 2022)
Each year the world produces more and more durable plastic waste, which is accumulating in nature. One of the solutions to ease its impact is to recycle and reuse it for new products and intermediate products. Recycled plastic, especially thermoplastic, has great potential in the wood industry. In our research, we have used waste coffee cups and spoons made of polystyrene to make two adhesive mixtures, using dimethylformamide as a solvent. To establish the shear strength of adhesive bonds, we made bonded wood panels according to the instructions by standard SIST EN 205:2016. The idea was to optimize the temperature of hot pressing and to add a cooling procedure to ensure better shear strength of the bond, which is needed to reach the minimum criteria of the SIST EN 204:2016 standard. We used two temperatures for hot pressing (150 °C and 120 °C) and four ways of panel cooling in a closed press. After trying out different procedures, we came to the conclusion that the best way to use a coffee cup adhesive is to cool it down to 75 °C, while for the spoon-based adhesive the best bonding method is to cool the joints down to 100 °C or 25 °C. We also found that by cooling the panels in a closed press the consistency of the results increases, which makes the adhesive bonds more reliable. We managed to reach standard criteria with a sample which had been glued with coffee cup adhesive, hot pressed at 150 °C and cooled down to 75 °C before being taken out of the press.
Keywords: gluing; adhesive bond; wood; polystyrene; recycling